Rates of insufficiency and deficiency of vitamin D levels in elite professional male and female skiers: A chronobiologic approach - Vitale, J. A.; Lombardi, G.; Cavaleri, L.; Graziani, R.; Schoenhuber, H.; La Torre, A.; Banfi, G. (Chronobiology International, 2018)
Vitamin D is essential for the maintenance and promotion of musculoskeletal health, for the functioning of the immune, cardiovascular and reproductive systems, and its main action is to keep calcium and phosphate plasmatic physiological concentrations at intestinal, renal and bony level. Vitamin D affects several parameters related to physical performance too and a particularly high percentage of vitamin D insufficiency and deficiency in professional athletes has been observed. Several variables are able to impair the synthesis of 25(OH)D in athletes, specifically both genetic and environmental factors, but the most probable explanation for the deficient/insufficient vitamin D levels is the insufficient ultraviolet B light (UVB) exposure during winter. To confirm this, the existence of a circannual rhythm of vitamin D in professional soccer players, highlighting a peak in summer and lowest values in winter regardless the period of the season, has been documented. Nonetheless, from what we are aware of, no other study adopted a chronobiologic approach to better understand and describe the circannual variations of serum 25(OH)D in other sport disciplines. Therefore, we studied serum vitamin D in a cohort of top-level professional skiers, during a period of three consecutive competitive seasons (2015, 2016 and 2017), in order to evaluate, with a rhythmometric approach, the vitamin D behavior along the year. The study population was composed by 152 professional Italian alpine skiers of FISI (Winter Sport Italian Federation), 63 females and 89 males (mean age: 24.1 ± 3.2 years) and a total of 298 blood drawings were carried out to determine plasma 25(OH)D. Vitamin D data were compared between genders and then processed with the population mean cosinor tests to evaluate the presence of a circannual rhythm, both for female and male athletes. In total, 77 skiers (50.7%) showed, at least once during the three competitive seasons, an insufficient level of 25(OH)D and other 45 subjects (29.6%) showed a deficient status; no differences were observed between genders (mean for females: 26.9 ± 8.1 ng/mL; mean for males: 27.4 ± 7.6 ng/mL). In addition, the rhythmometric analysis highlighted the existence of a significant circannual rhythm for both female and male professional skiers; the acrophases (F) occurred in July and both MESOR (M) and amplitude (A) were comparable between the two groups. Our data indicate that, despite the physical effort spent, vitamin D follows a classical season-associated rhythm with a peak in summer and a nadir in winter. Moreover, the percentage of insufficiency and deficiency is in line with that of the general population. In conclusion, our findings reinforce the hypothesis that there is no direct effect of physical activity on vitamin D metabolism and that the factors involved in the determination of vitamin D levels in the general population are valid also for athletes.